2020
DOI: 10.1371/journal.pone.0237735
|View full text |Cite
|
Sign up to set email alerts
|

Fitness information-seeking behavior among female university students: A qualitative study

Abstract: Obsession with the physique and appearance is a by-product of consumer societies. As such, fitness and slimming have now become major concerns of Iranian females. This study endeavors to elaborate on information-seeking behaviors among female students of Isfahan University of Medical Sciences concerning fitness. This study conducted in 2018, employs a qualitative approach using conventional content analysis. The research population includes female students of Isfahan University of Medical Sciences, 16 of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The scores of the rungs of the ladder were rated in multiples of 3, with the minimum and maximum possible scores of 3 and 27, respectively. Respondents were classified to be in a low (< 9), middle (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), or high (> 18) socio-economic status strata based on summative scores. All of the pen and paper instruments were administered in English language.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The scores of the rungs of the ladder were rated in multiples of 3, with the minimum and maximum possible scores of 3 and 27, respectively. Respondents were classified to be in a low (< 9), middle (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), or high (> 18) socio-economic status strata based on summative scores. All of the pen and paper instruments were administered in English language.…”
Section: Protocolmentioning
confidence: 99%
“…Thus, expanding the understanding of emerging adults' preference for physical activity information may help implement relevant physical activity-enhancing topics while considering their preferred sources [7]. Previous studies have investigated why emerging adults seek physical activity information and the sources where they seek such information [7][8][9]. However, most of these studies focussed on fitness and exercise and not physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…To suit their learning demands, undergraduate learners employ limited electronic information materials. According to research by Jalali et al (2020), undergraduate learners rely on the internet, with a majority accounting for more than 70% claiming to utilize search engines as their chief search technique. In contrast, they less frequently use electronic journals and databases, which was reported by about 10% of students.…”
Section: Finding From Previous Studiesmentioning
confidence: 99%
“…Even though several search engines are used to search for information on the Web is a bit easier, students still face navigation challenges because it requires intelligent search techniques to enable them to have access to appropriate resources and information (Howlader & Islam, 2019). Today, web browsers and search engines only perform routine search actions, leaving the user to do the brainwork (Jalali et al, 2020). Vaaler et al (2021) highlighted several internet skills, including using search engines to identify Web publications, tracing information using a variety of tactics, and assessing the utility of the material.…”
Section: Finding From Previous Studiesmentioning
confidence: 99%
“…This variability can be attributed to multiple factors, and the influence of social media has emerged as a noteworthy factor driving these changes [ 30 ]. Previous research has indicated that young adults use social media platforms as their primary source of nutritional information [ 31 , 32 , 33 ]. Al-Bisher and Al-Otaibi (2022) discovered an association between the use of such platforms to seek nutritional information and an elevated likelihood of experiencing eating concerns (ECs) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%